Direct numerical simulation of spray and dispersion of liquid fuel droplets - Slavinskaya, N.; Haidn, O.J. (Recent Contributions to Physics, 2023)
A review of the existing phenomenological models was carried out, which gives a deep understanding of the features and characteristics of the formation of spray and dispersion of a liquid jet. These models give insight into the mechanisms of primary and secondary atomization of a liquid jet by tracing the behavior of a single fuel droplet placed in a stationary gaseous medium. The paper uses the direct numerical simulation method to present the computer simulation results of the atomization, dispersion, and evaporation of octane and dodecane droplets. To describe the interfacial interactions and track the particle's shape and position in the dispersed phase, the volume of fluid (VOF) method was used, which belongs to the class of Eulerian methods and is a non-autonomous algorithm. According to the results of computational experiments on the study of the processes of spraying, dispersion, and evaporation of octane and dodecane, the optimal combustion mode was established. Obtained results in this work have scientific and practical applications in constructing the fundamental theory of combustion and designing the injection systems structure with optimal parameters.